VD_FINDINFO Jug / 2020 / 19 vom 29. Juni 2017 - VD Tribunal cantonal (2017)
DEMANDE ADRESSÉE À L'AUTORITÉ, DÉCISION D'IRRECEVABILITÉ, RÉVISIONDÉCISION, DÉFENSE D'OFFICE | 132 al. 1 let. b CPP (CH), 410 al. 1 let. a CPP (CH)